Experts evaluation of usability for digital solutions directed at older adults: a scoping review of reviews - Silva, Anabela G. (2021)
Background: it is important to standardize the evaluation and reporting procedures across usability studies to guide researchers, facilitate comparisons, and promote high-quality studies. A first step to standardizing is to have an overview of how experts-based usability evaluation studies are reported across the literature. Objectives: to describe and synthesize the procedures of usability evaluation by experts that are being reported to conduct inspection usability assessments of digital solutions relevant for older adults. Methods: a scoping review of reviews was performed using a five-stage methodology to identify and describe relevant literature published between 2009 and 2020 as follows: i) identification of the research question; ii) identification of relevant studies; iii) select studies for review; iv) charting of data from selected literature; and v) collation, summary, and report of results. The research was conducted on five electronic databases: PubMed, ACM Digital Library, IEEE, Scopus, and Web of Science. The articles that met the inclusion criteria were identified, and data extracted for further analysis, including evaluators, current usability inspection methods, and instruments to support usability inspection methods. Results: a total of 3958 articles were identified. After a detailed screening, 12 reviews matched the eligibility criteria. Conclusion: overall, we found a variety of unstandardized procedures and a lack of detail on some important aspects of the assessment, including a thorough description of the evaluators and of the instruments used to facilitate the inspection evaluation such as heuristics checklists. These findings suggest the need for a consensus framework on the experts’ assessment of usability that informs researchers and allows standardization of procedures.